Residual Effect of Lead on Early Growth of Fluted Pumpkin (Telfairia occidentalis Hook F) in an Ultisol - Orhue Ehi Robert; Uzu Frank; Ekhomun Akhere Mathew (Journal of Applied Sciences and Environmental Management)
The greenhouse and field trials were carried out at Faculty of Agriculture, University of Benin, Benin City to find out the residual influence of Pb on some Telfairia occidentalis agronomic characters and soil chemical properties. The soils used were previously treated with 0, 50, 100, 200 mg per 5 kg soil in the greenhouse while 0, 20, 40, 80 kgha-1 equivalent to that of greenhouse were used in the field trial. The soils were previously used for Telfairia occidentalis cultivation. The completely randomized and randomized complete block designs were used in greenhouse and field trials respectively. Results indicated that with the exception of N and K in the field trial all other soil nutrient components decreased inconsistently with increased Pb concentrations in the trials compared to pre-trial soil nutrient content. The Pb, N, P, K, Mg, Ca, Na, Fe, Mn, Zn and their uptake by the plant decreased significantly with increase in Pb concentrations. The crude protein content of the plant also reduced significantly with increased Pb concentrations. The dry matter yield, plant height, stem girth and number of leaves were depressed significantly by the Pb compared to the control. @JASEM